Simplemail business case: the dilemma of customer portfolio expansion - Torres, Juan Pablo; Morales, Patricio; Vidal, Juan Pablo; van Eijck, Peter (Estudios de Administración, 2013)
Simplemail is a company immersed in the field of correspondence that was born in 1995, is located and maintains to this day in the city of Santiago, Metropolitan Region. The company is led by its owner Pablo Rodríguez (CEO), who makes the strategic decisions of the company and is supported in daily activities by his mother, brother, and sister-in-law. To date, Simplemail has four clients (MTS, Punto Maestro, SCB, Construplaza), which it covers on time and in a personalized way. In June 2013 Pablo Rodríguez is faced with a capacity deficit to expand his client portfolio, as that after some attempts to expand it, they had great problems in the service they provided, losing those new customers. Logistical problems were the causes of the failure of the expansion. Pablo is sitting at his desk thinking about how to solve this problem in the next six months before meeting with the owner. He needs Simplemail to achieve greater loyalty and profitability, but he wonders: What activities could be causing efficiency problems and how can we measure and solve this?